2009
DOI: 10.1007/s12600-009-0022-y
|View full text |Cite
|
Sign up to set email alerts
|

Notes on pistachio seed wasps from two locations in the east Mediterranean

Abstract: Two seed wasps, Eurytoma plotnikovi Nikol'skaya.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The economic impacts of some Megastigmus invasions in Europe are important, especially for M. spermotrophus on Douglas-fir and M. schimitscheki on cedar, which receive considerable attention from forest and seed orchard managers (Jarry et al 1997;Fabre et al 2004). However, the possible ecological impacts of these alien seed chalcids on both the native flora and fauna have been largely overlooked because most of the studies have taken place in intensively-managed seed orchards and plantations, not in natural stands, either for conifers or angiosperms (Mailleux et al 2008;Doğanlar et al 2009). Indeed, most studies aimed at showing an ecological effect of invasive alien insects on native species have focused on groups that are considered important for the economy or public health (e.g.…”
Section: Pheromone Traps Established Inmentioning
confidence: 99%
“…The economic impacts of some Megastigmus invasions in Europe are important, especially for M. spermotrophus on Douglas-fir and M. schimitscheki on cedar, which receive considerable attention from forest and seed orchard managers (Jarry et al 1997;Fabre et al 2004). However, the possible ecological impacts of these alien seed chalcids on both the native flora and fauna have been largely overlooked because most of the studies have taken place in intensively-managed seed orchards and plantations, not in natural stands, either for conifers or angiosperms (Mailleux et al 2008;Doğanlar et al 2009). Indeed, most studies aimed at showing an ecological effect of invasive alien insects on native species have focused on groups that are considered important for the economy or public health (e.g.…”
Section: Pheromone Traps Established Inmentioning
confidence: 99%
“…Eurytoma plotnikovi is generally considered as one of the most harmful pests for this crop; for example, in Tunisia, Braham et al (2010) found it in 62 out of 87 surveyed orchards (mean infestation rate 42% of the trees in each orchard, range 1–96%). In the region of Gaziantep, Turkey, 69–81% of the fruits in untreated orchards were found to be infested (Doğanlar et al, 2009). In Iran, conversely, where it used to be considered as a major pest (Jalilvand & Gholipour, 2002), it now has only a minor impact in 95% of managed crops although it is abundant on wild trees (Mehrnejad, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…As alternative control measures, sanitation is of critical importance, by destroying the unharvested nuts which have fallen to the ground (Mehrnejad, 2020). Mehrnejad (2020) also indicates that no natural enemy is known, although Doğanlar et al (2009) report a 2–18% parasitism by Gugolzia karadagae (Hymenoptera: Pteromalidae) (Doğanlar & Doğanlar, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Diverse works have focused on describing the arthropods pests of pistachio in different countries [ 6 , 7 , 8 , 9 , 10 ]. Among the most damaging species are, for instance, the pistachio seed wasps Eurytoma plotnikovi Nikol’skaya (Hymenoptera: Eurytomidae) and Megastigmus pistaciae Walker (Hymenoptera: Torymidae) [ 11 , 12 ], the bark beetle Chaetoptelius vestitus (Mulsant and Rey) (Coleoptera: Curculionidae) [ 13 ], the pistachio psylla Agonoscena pistaciae Burckhardt and Lauterer (Hemiptera: Psyllidae) [ 14 ] and the lepidopteran species Choristoneura rosaceana (Harris) (Lepidoptera: Tortricidae), Amyelois transitiella (Walker) (Lepidoptera: Pyralidae) and Kermania pistaciella Amsel (Lepidoptera: Tineidae) [ 7 , 15 ].…”
Section: Introductionmentioning
confidence: 99%